Institutionalizing Moderate Islamic Legal Reasoning: An Istinbāṭ Framework for Contemporary Islamic Law - Ainol Yaqin; Muhid Muhid; Saude Saude; Muhammad Taufiq; Abdelmalek Aouich (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2026)
Contemporary Islamic legal discourse is often shaped by tensions between rigid textualism and unrestricted contextualism, creating challenges for developing legal rulings that are both normatively grounded and socially responsive. Although religious moderation and istinbāṭ al-aḥkām have been studied before, there has been no discussion on how moderation can be incorporated into this process. The current study aims at studying istinbāṭ approach where moderation becomes part of the process of producing legal rulings. In order to address the research objectives, a qualitative case study design was employed. Data collection was conducted using semi-structured interviews with 12 participants, non-participant observations in 8 sessions of legal reasoning, and analysis of institutional documents and fatwa books. As results show, religious moderation is perceived as a process whereby the balance between texts, context, and objectives of Islamic law is achieved. Religious moderation is operationalized through two approaches: the first is Qawlī Intiqādī, which includes critical evaluation and selection of juristic opinions, while the other is Manhajī and includes derivation of the rulings from texts, principles, and objectives of Islamic law. Moreover, the results show that the involvement of multiple actors in collective reasoning, consulting with different specialists, and considering the public welfare are important for arriving at context-sensitive legal rulings.